Sensitivity Analysis and Experimental Verification of Bolt Support Parameters Based on Orthogonal Experiment - Kun Zhang; Jinpeng Su; Zengkai Liu; Hongyue Chen; Qiang Zhang; Shaoan Sun (Shock and Vibration)
This paper presents a unified supporting parameter optimization procedure for the coupled bolt-rock systems by using the orthogonal experimental methods. Convergence of surrounding rock surface and deformations in the rock are taken as the objective functions for the stability of the surrounding rock of the roadway. The key support parameters of the bolt are considered as input variables. The simulation software FLAC3D is employed to develop the mechanical model for the coupled bolt-rock system and the objective functions of the coupled system are therefore obtained in the software. Combining the variance and multivariate linear regression analysis, an approach is derived to investigate the sensitivity of the support parameters to the objective functions. The corresponding support parameters are then optimized. The 15106 working of a practical mine in Yangquan is taken as an example. According to the similar simulation theory, corresponding simulation experiments are performed. Thus, the proposed method is validated and its robust performance for optimization of supporting parameters of the bolt is also demonstrated. The method provides a theoretical basis for the determination of bolt support parameters for mining roadway in a fully mechanized mining face.